2010
DOI: 10.1016/j.ecolmodel.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

A heuristic approach to predicting water beetle diversity in temporary and fluctuating waters

Abstract: a b s t r a c tAn understanding of the causal mechanisms and processes that shape macroinvertebrate communities at a local scale has important implications for the management and conservation of freshwater biodiversity. Here we compare the performance of linear and non-linear statistics to explore diversity-environment relationships using data from 76 temporary and fluctuating ponds in two regions of southern England. We focus on aquatic beetle assemblages, which have been shown to be excellent surrogates of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 76 publications
(87 reference statements)
0
15
0
Order By: Relevance
“…We found a positive correlation of pH and conductivity (Supporting Information Table S3), and at the same time decreasing abundances and species richness with increasing conductivity (Supporting Information S3). This is in line with the above outlined, corresponding effects of detritus on pH, but is in contrast to the observations of some studies in which rising conductivity was shown to have a positive effect on species richness (Eyre et al ., ; Heino, ; Bilton et al ., ), at least up to a threshold of around 600 μS (Gutiérrez‐Estrada & Bilton, ). Our results suggest that water bodies with lower abundances of water beetles and fewer species had conductivity levels exceeding this 600 μS threshold; however, there was no such clear threshold in our data set.…”
Section: Discussionmentioning
confidence: 99%
“…We found a positive correlation of pH and conductivity (Supporting Information Table S3), and at the same time decreasing abundances and species richness with increasing conductivity (Supporting Information S3). This is in line with the above outlined, corresponding effects of detritus on pH, but is in contrast to the observations of some studies in which rising conductivity was shown to have a positive effect on species richness (Eyre et al ., ; Heino, ; Bilton et al ., ), at least up to a threshold of around 600 μS (Gutiérrez‐Estrada & Bilton, ). Our results suggest that water bodies with lower abundances of water beetles and fewer species had conductivity levels exceeding this 600 μS threshold; however, there was no such clear threshold in our data set.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been shown for some groups (e.g. Coleoptera) that considering only higher taxonomic levels already allows the monitoring of water bodies (Criado and Alaez, 1995;Oertli et al, 2005a;Gutiérrez-Estrada and Bilton, 2010), detailed species identifications, which are often difficult and time-consuming, may not always be necessary. Nevertheless, if detailed species identifications are required, we consider DNA barcoding as a potential tool to overcome identification difficulties, such as shown for example by Hajibabaei et al (2011) for benthic freshwater macroinvertebrates.…”
Section: Aquatic Phasementioning
confidence: 99%
“…Many study emphasizes the comparison between model result in good prediction performance of ANN, whilst the used of linear models are of the less efficient model that might attribute to the non-linearity of the data sets (Thompson et al , [12]; Chaloulakou et al , [9]; Bandyopadhyay and Chattopadhyay, [7]; Sousa et al , [8]; Jahandideh et al , [10]; Gutierrez-Estrada and Bilton, [13]; Rossel and Behrens, [14]; Wu et al , [15]). ANNs are greatly suited to dynamic non linear system modelling (Mirsepassi, [16]) and have advantages over conventional simulation methods have been discussed in detail by French et al , [17].…”
Section: Introductionmentioning
confidence: 99%